Motion estimation of an aircraft model using computer vision - Kasula, Pavithra; Whidborne, James F.; Rana, Zeeshan A.; Ishola, Ademayowa (American Institute of Aeronautics and Astronautics (AIAA), 2024)
Dynamic wind tunnel tests are used to investigate the flight dynamics of aircraft. Currently contact measurement systems are used which increase friction and require on-board instrumentation. A vision-based method is proposed in this paper. The method uses a sequential process of Harris corner detection, Kanade-Lucas-Tomasi tracking, and Euler angles to identify the Euler angles from a pair of cameras, one with a top-view and the other with a side-view. The method is tested by simulating a 3D CAD model for a single degree of freedom rotational motion. The results have been quantified through numerical analysis and the proposed method is analysed analytically. The developed method is effective when integrated with another method of instrumentation such as an IMU.